2016
DOI: 10.1016/j.bjorl.2015.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Feeding methods for children with cleft lip and/or palate: a systematic review

Abstract: The studies show that prior to surgical repair, the use of alternative methods can be beneficial. In the postoperative period following lip repair, methods with suction are more beneficial. However, in the postoperative period of palatoplasty, there are divergences of opinion regarding the most appropriate feeding methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 26 publications
1
35
0
7
Order By: Relevance
“…Late introduction of food can cause weight loss and deficit of nutrients that are important for growth (26) . The time of introduction of pasty and solid foods observed in this study was adequate, in agreement with the ages suggested and described in the literature (26,27) . At the time of study completion, the preference of the participants for solid food suggests that the process of food introduction occurred properly as expected.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Late introduction of food can cause weight loss and deficit of nutrients that are important for growth (26) . The time of introduction of pasty and solid foods observed in this study was adequate, in agreement with the ages suggested and described in the literature (26,27) . At the time of study completion, the preference of the participants for solid food suggests that the process of food introduction occurred properly as expected.…”
Section: Discussionsupporting
confidence: 79%
“…These difficulties arise at birth, because of impairment of the functions of suction and swallowing (26,27) . CLP has been the focus of different clinical and epidemiological trials and case reports, but few have associated this anomaly with dysphagia so far.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, previous studies have confirmed this tendency, and the decline of the age of menarche in our country may reach up to 3.6 months per decade (7,8). Data regarding the age at which puberty begins and evolves in the Brazilian population are scarce (9,10). The most relevant study on this topic was performed in the 1980s (10).…”
Section: Introductionmentioning
confidence: 99%
“…First, a cleft of the palate impedes the creation of negative intraoral pressure during sucking [8], preventing nutritive sucking [9] and probably also reducing non-nutritive sucking acts such as pacifier use [2]. Second, surgeries in the orofacial area are frequently performed in the early stages of life (e.g., lip closure, palatal closure etc.).…”
Section: Introductionmentioning
confidence: 99%